Rheumatoid Arthritis Naive T Cells Share Hypermethylation Sites With Synoviocytes. Issue 3 (March 2017) - Rhead, Brooke; Holingue, Calliope; Cole, Michael; Shao, Xiaorong; Quach, Hong L.; Quach, Diana; Shah, Khooshbu; Sinclair, Elizabeth; Graf, John; Link, Thomas; Harrison, Ruby; Rahmani, Elior; et al.
Abstract : Objective: To determine whether differentially methylated CpGs in synovium‐derived fibroblast‐like synoviocytes (FLS) of patients with rheumatoid arthritis (RA) were also differentially methylated in RA peripheral blood (PB) samples. Methods: For this study, 371 genome‐wide DNA methylation profiles were measured using Illumina HumanMethylation450 BeadChips in PB samples from 63 patients with RA and 31 unaffected control subjects, specifically in the cell subsets of CD14+ monocytes, CD19+ B cells, CD4+ memory T cells, and CD4+ naive T cells. Results: Of 5, 532 hypermethylated FLS candidate CpGs, 1, 056 were hypermethylated in CD4+ naive T cells from RA PB compared to control PB. In analyses of a second set of CpG candidates based on single‐nucleotide polymorphisms from a genome‐wide association study of RA, 1 significantly hypermethylated CpG in CD4+ memory T cells and 18 significant CpGs (6 hypomethylated, 12 hypermethylated) in CD4+ naive T cells were found. A prediction score based on the hypermethylated FLS candidates had an area under the curve of 0.73 for association with RA case status, which compared favorably to the association of RA with the HLA–DRB1 shared epitope risk allele and with a validated RA genetic risk score. Conclusion: FLS‐representative DNA methylation signatures derived from the PB may prove to be valuable biomarkers for the risk of RA or for disease status.